A simplified multi-layered finite element model for flexible pipes. (January 2019) - Yoo, Dong-Hyun; Jang, Beom-Seon; Yun, Ran-Hui
Abstract: A flexible pipe connects offshore platforms to the flowlines and transport gas and oil. It may experience axial compression due to the reversed end cap effect during installation. This can trigger radial buckling or lateral buckling of tensile armor layers. The ultimate strength assessment of the flexible pipe is complicated and time-consuming due to material nonlinearity, large deformation, and nonlinear contact mechanism. These difficulties make the nonlinear analyses difficult to converge. This paper proposes a simplified 5-layered model which can improve the convergence without deteriorating the accuracy. Analytical methods are suggested to determine an equivalent layer to replace inner four layers. In addition, the factor of penetration tolerance (FTOL) of shell element layers needs to reflect the thinning of polymer layers, which makes the axial stiffness equal to the solid element model. Analytical methods are used to determine the factor and a stepwise increasing approach is applied in a numerical analysis. The 5-layered model with the stepwise FTOL application is verified by comparing with 8-layered model, analytical model and experiment results with respect to axial and bending stiffness. The model is used for an ultimate strength assessment, the failure mechanism and the interaction between layers are investigated in detail with incremental loading. Highlights: The ultimate strength assessment of the flexible pipe is very complicated and time-consuming. This paper proposes a simplified 5-layered model which can improve the convergence without deteriorating the accuracy. Analytical methods are suggested to determine an equivalent layer to replace inner four layers. The factor of penetration tolerance (FTOL) of shell element layers needs to reflect the thinning of polymer layers.